Juan Ossio, Etnografía de la cultura andina. Lima: Fondo Editorial del Congreso del Perú. 2018. 514 p. - Huerta-Mercado, Alexander (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
The book brings together the works carried out by Juan Ossio over fifty years; developed from his field research, analysis of historical documents and personal testimonies. The author uses the ethnographic and historical method to identify and analyze the common characteristics that articulate different aspects of economic, political, traditional, ritual and kinship organization in the communities of the Andean territory under cultural characteristics that approach a matrix.

El libro reúne los trabajos realizados por Juan Ossio a lo largo de cincuenta años; desarrollados a partir de sus investigaciones de campo, análisis de documentos históricos y testimonios personales. El autor se sirve del método etnográfico e histórico para identificar y analizar las características comunes que articulan diferentes aspectos de organización económica, política, tradicional, ritual y de parentesco en las comunidades del territorio andino bajo características culturales que se acercan a una matriz.
Juan Ossio, Ethnography of the Andean culture. Lima: Fondo Editorial del Congreso del Perú. 2018. 514 p.
Keywords: Andino; Cultura; Etnografía; Juan Ossio; https://purl.org/pe-repo/ocde/ford#5.04.03